Endodontic Irrigation Chemical disinfection of the root canal system - Basrani, Bettina; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book reviews the available information on bacterial disinfection in endodontics, with emphasis on the chemical treatment of root canals based on current understanding of the process of irrigation. It describes recent advances in knowledge of the chemistry associated with irrigants and delivery systems, which is of vital importance given that chemical intervention is now considered one of the most important measures in eliminating planktonic microbes and biofilms from the infected tooth. Recommendations are made regarding concentrations, exposure times, and optimal sequences. Possible complications related to the use of the different solutions are highlighted, with guidance on response. In addition, clinical protocols are suggested on the basis of both clinical experience and the results of past and ongoing research. Throughout, a practical, clinically oriented approach is adopted that will assist the practitioner in ensuring successful endodontic treatment.
Chapter 1. Microbial Biofilms in Endodontics -- Chapter 2. Update in Root Canal Anatomy of Permanent Teeth Using Microcomputed Tomography -- Chapter 3. Syringe Irrigation: Blending Endodontics and Fluid Dynamics -- Chapter 4. Research on Irrigation: Methods and Models -- Chapter 5. Update of Endodontic Irrigating Solutions -- Chapter 6. Complications of Endodontic Irrigation: Dental, Medical, and Legal -- Chapter 7. The Role of the Patency File in Endodontic Therapy -- Chapter 8. Manual Dynamic Activation (MDA) Technique -- Chapter 9. Apical Negative Pressure: Safety, Efficacy and Efficiency -- Chapter 10. Sonic and Ultrasonic Irrigation -- Chapter 11. Continuous Instrumentation and Irrigation: The Self-Adjusting File (SAF) System -- Chapter 12. Ozone Application in Endodontics -- Chapter 13. Irrigation of the Root Canal System by Laser Activation (LAI): PIPS Photon-Induced Photoacoustic Streaming -- Chapter 14. Photodynamic Therapy for Root Canal Disinfection -- Chapter 15. Local Applications of Antibiotics and Antibiotic-Based Agents in Endodontics -- Chapter 16. Intracanal Medication -- Chapter 17. Disinfection in Nonsurgical Retreatment Cases -- Chapter 18. Irrigation in Regenerative Endodontic Procedures -- Chapter 19. Conclusion and Final Remarks.
Keywords: Dentistry; Dentistry